Post-translational regulation of HD-Zip IV transcription factors in Arabidopsis - Subedi, Bibek (Kansas State University, 2022)
Class IV homeodomain leucine-zipper (HD-Zip IV) transcription factors (TFs) are master regulators of epidermal cell fate during embryonic and post-embryonic development in plants. GLABRA2 (GL2), the founding member of the HD-Zip IV TFs, plays critical roles in trichome and root hair development as well as in biosynthesis of anthocyanin, seed coat mucilage and seed oil. It has four defined domains including a DNA-binding homeodomain (HD), a leucine-zipper dimerization domain termed Zipper Loop Zipper (ZLZ), a Steroidogenic Acute Regulatory (StAR) protein-related lipid Transfer (START) domain, and a START-associated domain. Previous work demonstrated that the START domain of GL2 is involved in ligand binding and is required for TF dimerization, stability and activity. However, a detailed mechanism controlling the level of HD-Zip IV TFs in plants remains unknown. The overall goal of this project is to identify and characterize post-translational regulatory mechanisms affecting the turnover and activity of HD-Zip IV TFs in Arabidopsis. To determine protein half-lives, in vivo cycloheximide chase experiments were performed using Arabidopsis seedlings, uncovering a role for the ZLZ domain in destabilizing GL2. In addition, the Ubiquitin/26S proteasome system was implicated in the degradation of unstable GL2 protein resulting from START domain mutation. Next, bioinformatics tools predicted multiple, high confidence conserved ubiquitination and SUMOylation sites in the ZLZ domain of GL2 and the modifications were verified in vivo by performing immunoprecipitation experiments. Site-directed mutagenesis of the candidate amino acids resulted in a gain-of-function phenotype characterized by an increased frequency of abaxial leaf curling in lysine-to-arginine (K-R) mutants. In contrast to EYFP-tagged protein, plants expressing GL2 with a smaller 6x His 3x FLAG tag did not display leaf curling, suggesting that this phenotype is associated with increased protein stability. Ongoing experiments focus on RNA-Seq experiments to characterize the molecular mechanisms of abaxial leaf curling. In addition to ubiquitin and SUMO (small ubiquitin-like modifier) sites, two high confidence SUMO-interacting motifs (SIMs) were bioinformatically predicted in the GL2 START domain from Arabidopsis. SIMs are short hydrophobic sequences present in many proteins that can non-covalently bind to SUMO-conjugated proteins. Mutational analysis with confocal microscopy revealed defects in trichome branching and nuclear localization of the protein in SIM mutants. Yeast two-hybrid experiments failed to detect GL2-SUMO interactions as most of the Arabidopsis thaliana SUMO isoforms were not expressed in yeast. However, unlike wild-type protein, SIM mutants displayed impaired dimerization. These results indicate the role of SIMs in the subcellular localization and TF activity of GL2. Further experiments will be required to identify proteins that associate with GL2 through SUMO-SIM interactions. Overall, the findings suggest that regulatory mechanisms involving ubiquitin and/or SUMO contribute to GL2 levels and activity in plants. This work provides new insight into how the protein levels of critical transcriptional regulators of epidermal cell differentiation are fine-tuned in plants. The new knowledge will ultimately guide molecular toolkits for engineering HD-Zip IV TFs to establish more resilient and high yielding cultivars.
Keywords: Homeodomain leucine zipper; START domain; GLABRA2; Protein stability; Ubiquitination; Leaf curling